Prognosis of microwave ablation for hepatocellular carcinoma: does age make a difference? - Yi-Xuan Zhang (International Journal of Hyperthermia, 2020)
Objective Hepatocellular carcinoma (HCC) is a notable threat to the longevity of elderly people. However, there is no trial to study the prognosis of these elderly patients after microwave ablation (MWA) treatment. This study investigated whether elderly patients with HCC benefit from MWA similar to younger patients. Materials and methods Patients who underwent ultrasound-guided percutaneous MWA were included and divided into four age groups and the prognosis was compared. The senior group (Group S, ≥75 years) was then compared with the younger group (Group Y, <75 years) after a 1:1 propensity score matching was applied. The prognostic outcomes were evaluated and Cox analysis was performed to determine the factors associated with survival. Results The four age groups showed a statistically different distribution in terms of sex, size of liver nodules, and the Charlson comorbidity index. Although Group S had a higher Charlson comorbidity index, no significant differences were found between Group S and Group Y in the rates of complete ablation and major complications as well as overall survival and progression-free survival after matching. Cox analysis demonstrated that the size of tumors and Child Pugh grade rather than age or Charlson comorbidity index were significant prognostic factors for overall survival. Conclusion The elderly patients with HCC, even though associated with more comorbidities, may achieve acceptable prognostic outcomes following MWA, which are not worse than their younger counterparts.